Characterization of Hyperbolic Cylinders in a Lorentzian Space Form - Shu, Sh.; Han, Annie Yi (Журнал математической физики, анализа, геометрии, 2012)
We give a characterization of the n-dimensional (n ≥ 3) hyperbolic cylinders in a Lorentzian space form. We show that the hyperbolic cylinders are the only complete space-like hypersurfaces in an (n + 1)-dimensional Lorentzian space form M₁ⁿ⁺¹(c) with non-zero constant mean curvature H whose two distinct principal curvatures λ and μ satisfy inf(λ - μ)² > 0 for c ≤ 0 or inf(λ - μ)² > 0, H² ≥ c, for c > 0, where λ is of multiplicity n - 1 and μ of multiplicity 1 and λ < μ. Дается характеризация n-мерных (n ≥ 3) гиперболических цилиндров в лоренцевой пространственной форме. Показано, что гиперболические цилиндры являются единственными полными пространственноподобными гиперповерхностями в (n + 1)-мерной лоренцевой пространственной форме M₁ⁿ⁺¹(c) с ненулевой постоянной средней кривизны H, у которых две различные главные кривизны λ и μ удовлетворяют inf(λ - μ)² > 0 при c ≤ 0 или inf(λ - μ)² > 0, H² ≥ c, при c > 0, где λ имеет порядок n - 1, а μ порядок 1 и λ < μ.